A pilot study on School of Medicine students’ perception of ethical issues related to human specimens in anatomical museums - Ciliberti, Rosagemma; Lantieri, Francesca; Bagnara, Davide; Fais, Franco (Acta Biomedica Atenei Parmensis, 2024)
Background and aim: Anatomical museums provide an integrated and multidisciplinary education to address complex ethical issues. To date, studies investigating students’ attitudes toward preserved and displayed human remains in research laboratories is limited. The study aims to explore students’ emotional responses to anatomical collections preserved in university museums and the role that such museums can play in students’ ethical education. Methods: First-year medical students from the School of Medicine at the University of Genoa were invited to complete a questionnaire after a guided visit to the Museum of Human Anatomy in October 2023. Results: the 201 students who answered the questionnaire expressed high agreement on the retention and exhibition of human specimens and the learning opportunities it offers (91.7% and 97.3% of students, respectively). This high agreement also regarded the ethical issues related to their profession, with a high percentage of students considering this exposition an ethical learning opportunity (84.3%) and thinking that education in medicine should also imply ethical issues both in general (89.8%) and in regard to human specimens (86.1%). The agreement was also high regarding the ethical acceptability and importance of post-mortem donation of bodies for medicine education, although only 56.9% of responses indicate high agreement with post-mortem donation of their bodies to anatomical institutes. Conclusions: Overall, medical students express a significant positive interest in this educational context and its ethical acceptability. These data can impact medical education by shaping future teaching practices and integrating ethics into the medical curriculum.